Internationalization at Home (IaH) in Living-learning context - Kooi Cheng Lee; Swee Kit Alan Soong; Andi Sudjana Putra (University of Johannesburg, 2021)
Internationalisation has been associated with the cultivation of global competencies.  However, there have also been contentions about inclusivity, accessibility and mobility, and that it may privilege some.  This reflective piece attempts to respond to these tensions through a description of and reflection on the effectiveness of two Internationalisation at Home (IaH) initiatives.  It focuses on informal curricula in living-learning contexts where literature and concrete examples are scanty.  Drawing on the learning points, it shares thoughts about the need for critical mass, whole university experience, and intentionality.